Athletes and Hypertension - Schweiger, V.; Niederseer, D.; Schmied, C.; Attenhofer-Jost, C.; Caselli, S. (Current Cardiology Reports, 2021)
Purpose of Review: We reviewed most current medical literature in order to describe the epidemiology, clinical manifestation, outcome, and management of hypertension in athletes. Recent Findings: An estimated quarter of the world`s population is suffering from hypertension and this prevalence is also reflected in athletes and in individuals involved in leisure time sport activities. Several studies found an inverse relationship between physical activity and blood pressure. Therefore, physical exercise is recommended to prevent, manage, and treat hypertension. On the other hand, the prevalence of hypertension may vary by sport and in some cases may even be higher in athletes competing in certain disciplines than in the general population. Hypertension is the most common medical condition in athletes and may raise concerns about its management and the individual`s eligibility for competitive sports. A thorough clinical evaluation should be performed to correctly diagnose or rule out hypertension in athletes, describe the individual`s risk profile, rule out secondary causes, and detect possible hypertension-mediated organ damage caused by hypertension at an early stage. Based on most recent clinical research and international consensus documents, we propose a diagnostic algorithm as well the non-pharmacological and pharmacological management of hypertension in athletes. Summary: Although elevated blood pressure levels are less common in the active population, athletes are not protected from hypertension. A thorough diagnostic approach may help to identify individual at risk for adverse cardiovascular events and to address the optimal treatment as well as sport recommendations.